The relation between age and airway epithelial barrier function - de Vries, M.; Nwozor, K. O.; Muizer, K.; Wisman, M.; Timens, W.; van den Berge, M.; Faiz, A.; Hackett, T.-L.; Heijink, I. H.; Brandsma, C. A. (Respiratory research, 2022)
Background The prevalence of age-associated diseases, such as chronic obstructive pulmonary disease (COPD), is increasing as the average life expectancy increases around the world. We previously identified a gene signature for ageing in the human lung which included genes involved in apical and tight junction assembly, suggesting a role for airway epithelial barrier dysfunction with ageing. Aim To investigate the association between genes involved in epithelial barrier function and age both in silico and in vitro in the airway epithelium. Methods We curated a gene signature of 274 genes for epithelial barrier function and tested the association with age in two independent cohorts of bronchial brushings from healthy individuals with no respiratory disease, using linear regression analysis (FDR < 0.05). Protein–protein interactions were identified using STRING©. The barrier function of primary bronchial epithelial cells at air–liquid interface and CRISPR–Cas9-induced knock-down of target genes in human bronchial 16HBE14o-cells was assessed using Trans epithelial resistance (TER) measurement and Electric cell-surface impedance sensing (ECIS) respectively. Results In bronchial brushings, we found 55 genes involved in barrier function to be significantly associated with age (FDR < 0.05). EPCAM was most significantly associated with increasing age and TRPV4 with decreasing age. Protein interaction analysis identified CDH1 , that was negatively associated with higher age, as potential key regulator of age-related epithelial barrier function changes. In vitro, barrier function was lower in bronchial epithelial cells from subjects > 45 years of age and significantly reduced in CDH1 -deficient 16HBE14o-cells. Conclusion The significant association between genes involved in epithelial barrier function and age, supported by functional studies in vitro , suggest a role for epithelial barrier dysfunction in age-related airway disease.